Rotatable Aggregation‐Induced‐Emission/Aggregation‐Caused‐Quenching Ratio Strategy for Real‐Time Tracking Nanoparticle Dynamics - Wu, Hao; Zhang, Lu; Yang, Jinfan; Bo, Ruonan; Du, Hongxu; Lin, Kai; Zhang, Dalin; Ramachandran, Mythili; Shen, Yingbin; Xu, Yangxi; Xue, Xiangdong; Ma, Zhao; et al. (Advanced functional materials, 2020)
Real‐time tracking of the dynamics change of self‐assembled nanostructures in physiological environments is crucial to improving their delivery efficiency and therapeutic effects. However, such tracking is impeded by the complex biological microenvironment leading to inhomogeneous distribution. A rotatable fluorescent ratio strategy is introduced that integrates aggregation‐induced emission (AIE) and aggregation‐caused quenching (ACQ) into one nanostructured system, termed AIE and ACQ fluorescence ratio (AAR). Following this strategy, an advanced probe, PEG5k‐TPE4‐ICGD4 (PTI), is developed to track the dynamics change. The extremely sharp fluorescent changes (up to 4008‐fold) in AAR allowed for the clear distinguishing and localization of the intact state and diverse dissociated states. The spatiotemporal distribution and structural dynamics of the PTI micelles can be tracked, quantitatively analyzed in living cells and animal tissue by the real‐time ratio map, and be used to monitor other responsive nanoplatforms. With this method, the dynamics of nanoparticle in different organelles are able to be investigated and validated by transmission electron microscopy. This novel strategy is generally applicable to many self‐assembled nanostructures for understanding delivery mechanism in living systems, ultimately to enhance their performance in biomedical applications. A rotatable fluorescent ratio strategy that integrates aggregation‐induced emission and aggregation‐caused quenching into one nanostructured system, termed AAR, is introduced. Using this strategy, an advanced probe, PEG5k‐TPE4‐ICGD4, is developed to track the spatiotemporal distribution and structural dynamics of living cells and animal tissue.